A Case History Study of the Recycling Efforts from the United States Army Corps of Engineers Hurricane Katrina Debris Removal Mission in Mississippi - Dennis Leroy Brandon; Victor Frank Medina; Agnes Belinda Morrow (Advances in Civil Engineering)
In support of the Federal Emergency Management Agency (FEMA), the US Army Corps of Engineers (USACE) managed the removal of Hurricane Katrina storm debris in several states. This paper focuses on the debris removal practices in 16 southern Mississippi counties and the recycling efforts. Debris was removed from public and private property. The debris included vegetation, construction material, electronic waste, vehicles, and vessels. The scope of the USACE mission was expanded several times. The scope within the respective counties varied from vegetation only to the removal of every eligible form of debris. The recommendations proposed should enhance recycling efforts during future debris removal missions.